Development of wireless-based low-cost current controlled stimulator for patients with spinal cord injuries - Masdar, Aizan; Ibrahim, B. S. K. K.; Abdul Jamil, Mahadi (IEEE, 2012)
A spinal cord injury (SCI) has a severe impact on human life in general as well as on the physical status and condition. The use of electrical signals to restore the function of paralyzed muscles is called functional electrical stimulation (FES). FES is a promising way to restore mobility to SCI by applying low-level electrical current to the paralyzed muscles so as to enhance that person’s ability to function and live independently. However, due to the limited number of commercially available FES assisted exerciser systems and their rather high cost, the conventional devices are unaffordable for most peoples. It also inconvenient because of wired based system that creates a limitation in performing exercise. Thus, this project is concerned with the development of low-cost current controlled stimulator mainly for the paraplegic subjects. The developed device should be based on a microcontroller, wireless based system using Zigbee module, voltage-to-current converter circuit and should produce proper monophasic and biphasic current pulses, pulse trains, arbitrary current waveforms, and a trigger output for FES applications. The performances of the device will be assessed through simulation study and validated through experimental work. This device will be developed as in the new technique of the stimulator development with low cost and one of the contributing factors in Rehabilitation Engineering for patients with SCI.